KUALITAS LAPORAN KEUANGAN UKM DI KOTA PEKANBARU - Fenny Trisnawati, Jawanri Citra P. Situmorang (JURNAL AL-IQTISHAD, 2015)
The development of SMEs in the city of Pekanbaru are very rapidly both in urban and in rural areas. But there are still many SMEs whose management is not maximized both in managerially and financially. This study aims to determine how the quality of the financial statements of SMEs in the city of Pekanbaru. Taken 100 SME units in the city of Pekanbaru as sample. To determine the quality of the financial statements, there are thing that will be examined: (1) the presence or absence of accounting records, (2)  there is or is not doingthe recording and accounting reporting, (3) the presence or absence special part of routine accounting, (4) components of the financial statements. The results showed that as many as 84% of SME businessmen keep records of transactions, but only 61% were  making financial recordingregularly.  As many as 10% of SMEs have a special section which carry the recording and reporting of accounting. Only 1% of employers that presents the components of the complete financial statements. The majority of SMEs are as much as 32% present a statement of financial position and income statement in the financial statements. This suggests that the low quality of the financial statements of SMEs in Pekanbaru that reflects a lack of understanding and knowledge of the importance of accounting for business continuity support.